Putative genes of a variant-specific antigen gene transcription unit in Trypanosoma brucei - Alexandre, S.; Guyaux, M.; Murphy, N.B.; Coquelet, H.; Pays, A.; Steinert, M.; Pays, E. (Informa UK Limited, 1988)
In a 7-kilobase (kb) sequence upstream from the 5' barren region, the Trypanosoma brucei AnTat 1.3A expression site carries two putative genes, named ESAG 2 and ESAG 3 for expression site-associated genes, as well as a copy of ESAG 1 (D.F. Cully, H.S. Ip, and G.A.M. Cross, Cell 42:173-182, 1985). At least 3 kb of this expression site exhibits a high degree of homology with the silent telomere carrying the AnTat 1.3A basic copy, whose ESAG 1 is interrupted by stop codons. Like the antigen gene, the region containing the ESAGs is transcribed only in the bloodstream forms, although transcription of 5' barren- and ESAG 2-related sequences also occurs in cultured procyclics. Analysis of steady-state and nascent transcripts suggests a continuous transcription of the whole expression site by an RNA polymerase resistant to alpha-amanitin, possibly initiating at a polymerase I-like promoter located about 17 kb upstream from the antigen gene. This polymerase seems prone to becoming inactivated upon incubation of the trypanosomes at low temperature. The putative protein encoded by ESAG 3 may carry a hydrophobic signal peptide, suggesting interaction with a membrane.